Intervention for Patients Intubated and Conscious to decrease Peritraumatic Distress (IPIC-PTD) – Acceptability and feasibility - Gosselin, Émilie; Gélinas, Céline; Bourgault, Patricia; Lavoie, Stéphan (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2018)
Introduction. Keeping patients conscious while mechanically ventilated in intensive care has been shown to improve physical health but also to potentially cause peritraumatic distress and posttraumatic stress disorder. Risk factors for onset of psychological consequences in this population include bothersome symptoms, such as anxiety, delirium, pain, and sleep alteration. Objective. The objective of this study was to describe the acceptability and feasibility of a nursing intervention to prevent onset of peritraumatic distress and post-traumatic stress disorder in conscious intubated patients in intensive care unit by decreasing their bothersome symptoms. Methods. A descriptive design was used to document the perspective of patients (n=9) exposed to the intervention and of the interventionists (n=4) who delivered it. Data on acceptability and feasibility were collected through a self-administered questionnaire completed by participants and from researchers’ field notes. Results. The intervention was deemed acceptable and feasible by patients and interventionists in the intensive care unit environment. Intervention delivery fidelity was maintained by the dedicated interventionists participating in this pilot study. Discussion and conclusion. Mixed-design studies should be undertaken to further document the barriers to and facilitators of intervention implementation in a clinical intensive care unit context and to describe the mechanisms underlying intervention efficacy.